“BE CLOSE!”: SERVICE OF MILITARY CHAPLAINS DURING THE RUSSIAN-UKRAINIAN WAR (2014-2022) (Религиски дијалог и соработка, 2023)
The armed aggression of the Russian Federation, which began in 2014, drew theattention of society and religious institutions to the Armed Forces of Ukraine and revealedproblems in the establishing and developing the institution of military chaplaincy. Thisstudy aims to assess the basics of spirituality and practice, mission and functions of chaplaincyin the Russian-Ukrainian war. It was found that according to their main credo “Beclose!”, military chaplains have become an integral part of the military teams providingspiritual and moral support for military personnel. The activity of military chaplains extendsfar beyond direct service in military units in the combat zone or their deployment inUkraine. Military chaplains became volunteers who 1) coordinate and deliver humanitarianaid to the military and civilians, 2) maintain contacts with the families of servicemen,wounded and demobilized soldiers, 3) initiate the creation of special programs of spiritualrenewal at monasteries, rehabilitation courses at church communities, social events, etc.The chaplains have shown the readiness to resist the challenges of a new phase of largescalemilitary invasion of Ukraine by the Russian Federation since February 2022. Thereare no analogies in contemporary history of creating an institute of military chaplaincyunder such conditions that makes the current experience of Ukrainian chaplaincy unique.